The effect of board thickness on the screw stiffness of a PSSDB floor panel - Nur Shahidah, Mat So'd @ Mohd So'd (2014)
Rapid development in construction industry has resulted in increasing to demand for effective and innovative construction systems. Nowadays, construction no longer depends on current systems such as using timber bases and reinforcement concrete structures There are many problems with the current techniques such as high costing, low quality, and long construction time. One of the viable solution is to employ Industrialised Building System (IBS) which is a more efficient construction technology. Profiled Steel Sheeting Dry Board (PSSDB) is one type of Industrialised Building System (IBS). The PSSDB is a composite system that comprises of two main components which are profiled steel sheeting (PSS) and dry board (DB). They are attached by self drilling and self tapping screws. This research study about the effect of Primaflex dry board thickness towards the screw stiffness which has not been done before. The objectives of this study are to identify the screw stiffness using Primaflex dry board from push out test and to evaluate and also identify effect of Primaflex with different thicknesses. The results from this study have two parts which are effect of dry board from different thickness and effect of the screw. The result show that the Pnmaflex that has 9mm of thickness has higher screw stiffness (0.46 kN) than Primaflex that has 6mm of thickness (0.40 kN). Moreover, the result of an effect of the screw, the screw is easy to fail when the thickness of Primaflex is 6mm more than Primaflex 9mm. It is because, the hold between Peva and Primafl'ex is strong when the dry board is thick. As a conclusion, the thick board has a higher stiffness than thin board.